Fairgoers’ Attitudes Toward Youth Livestock Exhibits at the California State Fair - Krista Anderson-McCoon; Dwayne Cartmell; Robert Terry Jr. (Journal of Applied Communications, 2016)
Developing public and policy maker understanding of agriculture and natural resources is a national research priority of the American Association for Agricultural Education. Because of cultural and geographic distancing from agriculture, consumers' ability to obtain firsthand knowledge of agriculture may be limited to a handful of experiences including local, county, and state fairs. As such, agriculturalists' opportunities to communicate with the public about production agriculture may be limited to these experiences. Youth livestock exhibitors fill a gap in the agricultural education system. While a body of research exists about agricultural literacy among youth and adult groups, few studies exist concerning the impact of youth livestock show exhibits upon fairgoers. This study employed a survey research method using semantic differential scales with a then-now approach. Fairgoers, who had been through the youth livestock exhibits at the California State Fair, were asked about their attitudes toward the exhibits. Findings led to the conclusion viewing livestock exhibits and interacting with youth exhibitors resulted in fairgoers having more positive attitudes toward animal agriculture. Interaction between fairgoers and livestock exhibits should be encouraged and exhibitors should be prepared to view interactions with fairgoers as opportunities to educate about agriculture.
Keywords: California; Fair; Literacy; Livestock Exhibits; Semantic Differential; Youth